2004
DOI: 10.1261/rna.5222504
|View full text |Cite
|
Sign up to set email alerts
|

Template-dependent incorporation of 8-N3AMP into RNA with bacteriophage T7 RNA polymerase

Abstract: UV-induced photochemical crosslinking is a powerful approach that can be used for the identification of specific interactions involving nucleic acid-protein and nucleic acid-nucleic acid complexes. 8-AzidoATP (8-N 3 ATP) is a photoaffinity-labeling agent which has been widely used to elucidate the ATP binding site of a variety of proteins. However, its true potential as a photoactivatable nucleotide analog could not be exploited due to the lack of 8-azidoadenosine phosphoramidite, a monomer used in the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…Solid‐phase synthesis, most widely used for the synthesis of modified oligonucleotides, has limits in the preparation of longer RNAs of high purity, a limitation that in vitro transcription by T7 RNA polymerase does not face. T7 RNA polymerase mutants allow incorporation of modified nucleotides including dNTPs, 8‐azido ATP, 2′‐fluoro and 2′‐amino modified rNTPs . However, incorporation of a modified nucleotide at a single position at will is difficult with enzymatic synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Solid‐phase synthesis, most widely used for the synthesis of modified oligonucleotides, has limits in the preparation of longer RNAs of high purity, a limitation that in vitro transcription by T7 RNA polymerase does not face. T7 RNA polymerase mutants allow incorporation of modified nucleotides including dNTPs, 8‐azido ATP, 2′‐fluoro and 2′‐amino modified rNTPs . However, incorporation of a modified nucleotide at a single position at will is difficult with enzymatic synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously reported that the use of Mn 2+ as a cofactor in transcription reactions is beneficial for modulating the substrate specificity of RNA polymerases [ 32 ]. Furthermore, substrate specificity is even more improved by including a combination of Mg 2+ and Mn 2+ in the reaction; thus, both ions were added in performed experiments [ 33 ]. In the presented studies, all four RNA polymerases failed to produce a full-length transcript; however, shorter intermediate products were observed ( S3A–S3E Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Manganese ions decrease the substrate discrimination for many polymerases ( 22 ). T7 RNA polymerase can use Mn 2+ instead of Mg 2+ for catalysis; the optimum concentration of Mn 2+ is 2.0–2.5 mM ( 23 ), 10-fold lower than the optimum concentration of Mg 2+ . However, even at the optimum metal concentrations, the activity of T7 RNA polymerase with Mn 2+ is much lower than that with Mg 2+ ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, even at the optimum metal concentrations, the activity of T7 RNA polymerase with Mn 2+ is much lower than that with Mg 2+ ( 13 ). A mixture of Mn 2+ and Mg 2+ ions has been used successfully ( 23 , 24 ) to provide the two metal ions required for catalysis in the T7 RNA polymerase active site ( 17 ). Presumably, some T7 RNA polymerase molecules will have one Mn 2+ and one Mg 2+ in their active sites, resulting in relaxed specificity for substrate analogs.…”
Section: Resultsmentioning
confidence: 99%